Training the next generation of clinical researchers: evaluation of a graduate podiatrist research internship in rheumatology. - Naidoo, S; Bowen, C; Arden, N; Redmond, A (2013)
BACKGROUND: The aim of this study was to evaluate the effectiveness of the Arthritis Research UK funded graduate internship scheme for podiatrists and to explore the experiences of interns and mentors. METHODS: Nine new graduates completed the internship programme (July 2006-June 2010); six interns and two mentors participated in this study. The study was conducted in three phases. Phase 1: quantitative survey of career and research outcomes for interns. Phase 2 and 3: qualitative asynchronous interviews through email to explore the experiences of interns and mentors. Interpretive phenomenological analysis (IPA) of coded transcripts identified recurring themes. RESULTS: Research outputs included ten peer reviewed publications with authorial contributions from interns, 23 conference abstract presentations and one subsequent 'Jewel in the Crown' award at the British Society for Rheumatology Conference. Career progression includes two National Institute for Health research (NIHR) PhD fellowships, two Arthritis Research UK PhD fellowships, one NIHR Master of Research fellowship and one specialist rheumatology clinical post. Two interns are members of NIHR and professional body committees.Seven important themes arose from the qualitative phases: perceptions of the internship pre-application; internship values; maximising personal and professional development; psychosocial components of the internship; the role of mentoring and networking; access to research career pathways; perceptions of future developments for the internship programme. The role of mentorship and the peer support network have had benefits that have persisted beyond the formal period of the scheme. CONCLUSIONS: The internship model appears to have been perceived to have been valuable to the interns' careers and may have contributed significantly to the broader building of capacity in clinical research in foot and ankle rheumatology. We believe the model has potential to be transferable across health disciplines and on national and international scales.